2016
DOI: 10.1111/jphp.12543
|View full text |Cite
|
Sign up to set email alerts
|

Clobetasol-loaded nanostructured lipid carriers for epidermal targeting

Abstract: NLC proved to be a system with potential for targeting drug delivery to the epidermal layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 34 publications
0
17
0
1
Order By: Relevance
“…Formulations showed no micrometric clusters, even those containing the cationic polymer. Such finding contributes to the hypothesis by which the interaction between cationic polymer and anionic nanoparticles occurred as a coating process, leaving a homogeneously dispersed system, as also observed by Silva et al …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Formulations showed no micrometric clusters, even those containing the cationic polymer. Such finding contributes to the hypothesis by which the interaction between cationic polymer and anionic nanoparticles occurred as a coating process, leaving a homogeneously dispersed system, as also observed by Silva et al …”
Section: Resultsmentioning
confidence: 93%
“…Some studies have indeed reported the production of coated nanosystems by adding the polymer in the nanoparticle aqueous dispersion . In a previous study, we observed a nanoparticle increase from 124.56 to 257.5 nm after Ch coating . In this study, the percentage of Ch added to the system was higher, as the intention was to increase the viscosity rather than alter the own nanosystem.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include a ciclopirox nail lacquer with a water-soluble hydroxypropyl chitosan base (Onytec) 43 and econazole liposomal formulation (Pevaryl cream and generics). 44 In addition to the technologies described above, there are others that can be applied to dermatologic antifungal drug products to improve their effectiveness, 45 such as physical methods to promote drug permeation or accumulation, as iontophoresis 46 and microneedles 47 or formulation modifications as liposomal preparations, 48 which enhance skin deposition, nanostructured lipid carriers that can direct the drug to specific skin layers, 49,50 chitosan nanoparticles that provide an increased interval between product administrations, 51 and solid lipid nanoparticles and nanostructured lipid carriers that enhance nail hydration and drug penetration into the nail plate in onychomicosis treatments. 4 Thus, there is a clear space for development of better and novel topical antifungal products in both countries.…”
Section: Discussionmentioning
confidence: 99%
“…Hybridization enables the development of smart formulations or pharmaceutical forms that are able to specifically interact with biological barriers, 17 such as the mucosal tissues and skin. There are some reports of lipid-biopolymer hydrogels for the topical sustained release of ibuprofen, 18 ketoprofen, 19 ofloxacin, 20 Resina draconis, 21 clobetasol, 22 and LAs, [23][24][25] which exhibited optimized properties in comparison to their lipid-related DDS.…”
Section: Introductionmentioning
confidence: 99%